2015
DOI: 10.1136/bmjdrc-2014-000058
|View full text |Cite
|
Sign up to set email alerts
|

Lower levels of 25-hydroxyvitamin D3are associated with a higher prevalence of microvascular complications in patients with type 2 diabetes

Abstract: ObjectiveLow levels of serum 25-hydroxyvitamin D [25(OH)D] are commonly found in type 2 diabetes. We examined whether there is an association between circulating 25(OH)D concentrations and the presence of microvascular complications in people with type 2 diabetes.Research design and methodsWe studied 715 outpatients with type 2 diabetes who regularly attended our clinic. Participants were evaluated for the presence of microvascular complications (namely retinopathy and/or nephropathy) by clinical evaluation, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 41 publications
(40 reference statements)
5
46
2
1
Order By: Relevance
“…Inadequately controlled DM precipitates various long-term microvascular (blindness, n e p h r o p a t h y, a n d n e u r o p a t h y ) a n d macrovascular (cardiovascular and stroke) complications (1,2), which forms the leading cause of morbidity and mortality in patients of VDD has been associated with increased risk of chronic diseases, such as cancer, T2DM, cardiovascular disease, and autoimmune diseases including T1DM and multiple sclerosis, as evident from epidemiologic studies (1,8,18). N u t r i t i o n a l s t a t u s , p a r t i c u l a r l y micronutrients, might influence the risk for DR by affecting the biochemical mechanisms underlying DR (1,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequately controlled DM precipitates various long-term microvascular (blindness, n e p h r o p a t h y, a n d n e u r o p a t h y ) a n d macrovascular (cardiovascular and stroke) complications (1,2), which forms the leading cause of morbidity and mortality in patients of VDD has been associated with increased risk of chronic diseases, such as cancer, T2DM, cardiovascular disease, and autoimmune diseases including T1DM and multiple sclerosis, as evident from epidemiologic studies (1,8,18). N u t r i t i o n a l s t a t u s , p a r t i c u l a r l y micronutrients, might influence the risk for DR by affecting the biochemical mechanisms underlying DR (1,3).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from some recent studies show a significant inverse association between 25-hydroxyvitamin D [25 (OH)D] levels and the prevalence of diabetic microangiopathy, thus suggesting that VD and microvascular complications are strictly interrelated. Nonetheless, whether lower levels of VD are the cause or result of the microvascular complications are currently unknown (2). Moreover, the possible role of vitamins in the pathogenesis of diabetic complications is of much interest (8).…”
Section: Discussionmentioning
confidence: 99%
“…He et al (2014) and thus, conflicted with our study result. According to the study by Zoppini et al (2015), the multiple logistic regression analysis showed that there were significant association of high vitamin D with reduced risk of diabetic retinopathy and that of longer duration of diabetes with increased risk of diabetic retinopathy. The dissimilarities of these two study results with our study findings indicate that a multi-institutional large sample case-control study is needed to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mediating bone metabolism by regulating calcium and phosphorus homeostasis, vitamin D also modulates cell proliferation, differentiation, apoptosis, immune function, inflammation response, as well as vascular and metabolic properties (e.g., insulin secretion and insulin sensitivity) [12][13][14]. In the past few years, the association between vitamin D deficiency (VDD) and other nonclassical outcomes besides skeletal disorders has drawn increasing attention, especially diabetes and diabetes-related complications [14][15][16][17]. Although the inverse association between vitamin D levels and risk of T2DM [18,19], DR [20], DKD [21], or DFU [22] among diverse populations has been reported, uncertainties still exist due to the discordant results [23,24].…”
Section: Introductionmentioning
confidence: 99%